Existence of weak solutions for strongly damped wave equations with variable exponents (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
This work is concerned with a viscoelastic equation with strongly damping and variable exponents. The existence of weak solutions is established to the initial and boundary value problem under suitable assumptions by using the Faedo-Galerkin method and embedding theory.